Going Viral: News Sharing and Shared News in Social Media - Wadbring,Ingela (2016)
Through the advent of social media, news achieves a life of its own online. The media organisations partly lose control over the diffusion process, and simultaneously individuals gain power over the process, and become opinion leaders for others. This study focuses on news sharers and news shared (or rather, interacted), and has three RQ:s: 1) What characterizes the people who share news in social media, 2) Have the characteristics of interacted news changed over time? and 3) Are there differences between news content interacted by ordinary people and news highlighted by media organisations? Two different studies have been conducted: A representative survey and a quantitative content analysis. The main results are that the opinion leaders differ from the majority by being younger, with a greater political interest, single and more digital in their general lifestyle, both concerning news consumption and other aspects. The content analysis shows that the most interacted news on social media follow the traditional news values rather well, with a few exceptions. Most apparent is that interacted news is more positive over time and compared to print front-page news. Accidents and crime dominate print front-pages, while politics is more prominent in interacted news.